Self-monitoring composite rods for sustainable construction - Fangueiro, Raúl (2010)
This paper presents the development and properties assessment of braided reinforced composite rods (BCR) able to both reinforce and monitor the stress state of concrete infrastructures. The research study aims at understanding the tensile behaviour and self-monitoring ability of composite rods reinforced by a textile structure – braided structure with core reinforcement – for civil engineering applications, namely for concrete internal reinforcement, as a steel substitute, in order to improve structures safety and sustainability. Seven types of braided composite rods have been produced using an author patented technique based on a modified conventional braiding machine. The tensile properties of the braided reinforced composite rods were evaluated in order to identify the type(s) of fibre(s) to be used as core reinforcement. BCR have been tested under bending while the variation of the electrical resistance was simultaneously monitored.